Scoping review of registration of observational studies finds inadequate registration policies, increased registration, and a debate converging toward proregistration - Malmsiø, Daniel; Norlén, Simon; Jespersen, Cecilie; Neesgaard, Victoria Emilie; Song, Zexing; Chan, An-Wen; Hróbjartsson, Asbjørn (Journal of clinical epidemiology, 2025)
We aimed to examine a) the policies of national and international clinical trial registries regarding observational studies; b) the time trends of observational study registration; and c) the published arguments for and against observational study registration. Scoping review of registry practices and published arguments. We searched the websites and databases of all 19 members of the World Health Organization's Registry Network to identify policies relating to observational studies and the number of observational studies registered annually from the beginning of the registries to 2022. Regarding documents with arguments, we searched Medline, Embase, Google Scholar, and top medical and epidemiological journals from 2009 to 2023. We classified arguments as “main” based on the number (n ≥ 3) of documents they occurred in. Of 19 registries, 15 allowed observational study registration, of which seven (35%) had an explicit policy regarding what to register and two (11%) about when to register. The annual number of observational study registrations increased over time in all registries; for example, ClinicalTrials.gov increased from 313 in 1999 to 9775 in 2022. Fifty documents provided arguments concerning observational study registration: 31 argued for, 18 against, and one was neutral. Since 2012, 19 out of 25 documents argued for. We classified nine arguments as main: five for and four against. The two most prevalent arguments for were the prevention of selective reporting of outcomes (n = 16) and publication bias (n = 12), and against were that it will hinder exploration of new ideas (n = 17) and it will waste resources (n = 6). Few registries have policies regarding observational studies; an increasing number of observational studies were registered; there was a lively debate on the merits of registration of observational studies, which, since 2012, seems to converge toward proregistration. •Only 7 (35%) study registries had an explicit policy for observational studies.•Only 2 (11%) registries specified when to register observational studies.•The annual number of observational study registration increased in all registries.•The debate on observational study registration converges toward pro-registration.